Extraction of fuel from municipality solid wastes using an updraft gasifier - Wazed, M.A.; Ahmed, S. (2011)
In Bangladesh, cities are confronted with the problem of how to dispose large quantities of municipal solid waste (MSW). Gasification is a process that uses heat, pressure and steam to convert materials (MSW) directly into a gas composed primarily of carbon monoxide and hydrogen. The main objectives of this paper are: 1) to study gasification processes; 2) to design, fabrication and performance evaluation of a simple, in terms of cost, operation and maintenance, updraft gasifier; 3) production of combustible gases from municipality solid wastes using the manufactured updraft gasifier. In this research, an updraft gasifier is designed and fabricated. Mixture of gases is produced from municipality solid wastes using the updraft gasifier. In the mixture of gases, the presence of combustible elements are identified. In addition, the temperatures at six different and separate zones of the gasifier are measured and the variation in their values with time interval has been analysed. The constructed updraft gasifier is working well and the disparity pattern of the experimental temperature distribution at different and separate distinct zones and that of the reported patterns in earlier publications is consistent with each other in terms of quality.